Perspectives on Emerging Zoonotic Disease Research and Capacity Building in Canada. Issue 6 (1st December 2004) - Stephen, Craig; Artsob, Harvey; Bowie, William R; Drebot, Michael; Fraser, Erin; Leighton, Ted; Morshed, Muhammad; Ong, Corinne; Patrick, David
Abstract : Zoonoses are fundamental determinants of community health. Preventing, identifying and managing these infections must be a central public health focus. Most current zoonoses research focuses on the interface of the pathogen and the clinically ill person, emphasizing microbial detection, mechanisms of pathogenicity and clinical intervention strategies, rather than examining the causes of emergence, persistence and spread of new zoonoses. There are gaps in the understanding of the animal determinants of emergence and the capacity to train highly qualified individuals; these are major obstacles to preventing new disease threats. The ability to predict the emergence of zoonoses and their resulting public health and societal impacts are hindered when insufficient effort is devoted to understanding zoonotic disease epidemiology, and when zoonoses are not examined in a manner that yields fundamental insight into their origin and spread. Emerging infectious disease research should rest on four pillars: enhanced communications across disciplinary and agency boundaries; the assessment and development of surveillance and disease detection tools; the examination of linkages between animal health determinants of human health outcomes; and finally, cross-disciplinary training and research. A national strategy to predict, prevent and manage emerging diseases must have a prominent and explicit role for veterinary and biological researchers. An integrated health approach would provide decision makers with a firmer foundation from which to build evidence-based disease prevention and control plans that involve complex human/animal/environmental systems, and would serve as the foundation to train and support the new cadre of individuals ultimately needed to maintain and apply research capacity in this area.